Dynamic bridging modeling for coarse grained simulations of shock driven turbulent mixing. (15th March 2020) - Grinstein, F.F.; Saenz, J.A.; Rauenzahn, R.M.; Germano, M.; Israel, D.M.
Highlights: Simulation of material interpenetration, hydrodynamical instabilities, and mixing. Resolution of multiscale variable density turbulence and multiple shock transitions. Transition resolvable by LES/ILES but not by equilibrium single-point-closure RANS. Dynamic ILES/RANS bridging paradigm for variable-density turbulent mixing developed. Paradigm proofs of concept in transition and shock-driven turbulent mixing prototypes. Abstract: We focus on simulating the consequences of material interpenetration and mixing arising from perturbations at shocked material interfaces, as vorticity is introduced by the impulsive loading of shock waves, e.g., as in Inertial Confinement Fusion (ICF) capsule implosions. The flow physics is driven by flow instabilities such as Richtmyer-Meshkov, Kelvin-Helmholtz, Rayleigh-Taylor, and vortex stretching; it is capturable with both, classical large-eddy simulation (LES) and implicit LES (ILES) – where small-scale flow dynamics is presumed enslaved to the dynamics of the largest scales. Beyond the complex multiscale resolution issues of shocks and variable density turbulence, we must address the difficult problem of predicting flow transitions promoted by energy deposited at the material interfacial layers during the shock interface interactions. Transition involves unsteady large-scale coherent-structure dynamics resolvable by the coarse grained simulation but not by Reynolds-Averaged Navier-Stokes (RANS) modeling based on equilibrium turbulence assumptions and single-point-closures. We describe a dynamic blended hybrid RANS/LES bridging strategy for applications involving variable-density turbulent mixing applications. We report progress testing implementation of our proposed computational paradigm for relevant canonical problems, in the context of LANL's xRAGE Eulerian hydrodynamics and BHR unsteady RANS code. Proof-of-concept cases include the Taylor-Green vortex – prototyping transition to turbulence, and a shock tube experiment – prototyping shock-driven turbulent mixing.